Using Patient Perspectives to Inform the Development of a Behavioral Intervention for Chronic Pain in Patients with HIV: A Qualitative Study. Issue 5 (14th July 2016) - Merlin, Jessica S.; Young, Sarah R.; Johnson, Mallory O.; Saag, Michael; Demonte, William; Modi, Riddhi; Shurbaji, Sally; Anderson, William A.; Kerns, Robert; Bair, Matthew J.; Kertesz, Stefan; Davies, Susan; et al.
Abstract : Background . Chronic pain is a common and disabling comorbidity in individuals living with HIV. Behavioral interventions are among the most effective and safe nonpharmacologic treatments for chronic pain. However, the success of a behavioral intervention is influenced by how well it is tailored to the target population's biological, psychological, and social context. Given well-documented psychosocial vulnerabilities among persons with HIV, it is critical to develop a behavioral intervention for chronic pain tailored to this population. Objective . To use qualitative methods to investigate patient preferences for the structure and delivery of a behavioral intervention for chronic pain in individuals with HIV. Methods . Interviews and focus groups were used to elicit participant preferences. A thematic analysis approach, with an initial round of open coding, was used to develop the codebook and analyze the data. Results . Qualitative data from 12 interviews and 3 focus groups with patients living with HIV and chronic pain (total N = 24) were analyzed. Emergent themes fell into four major categories: perceived value of group sessions, incorporating peer leadership, and two key elements of how the intervention should be delivered: the HIV status of group participants and views on phone-delivered intervention content. Discussion . This study provides a framework for the structure and delivery of a behavioral intervention for chronic pain in individuals with HIV based on patient preferences. We will use these results to design our intervention, and hope that our approach informs the work of investigators in other disciplines who seek to incorporate patient preferences during intervention development.